Understanding probation periods: Benefits, challenges, and best practices in workforce management. - Chong Yin, Ching; Ismail , Fadillah (Journal of Islamic, Social, Economics and Development, 2025)
In most of the organization, success cannot leave without workers. However, human resource department faced problems in labour shortages, hard to find and recruit skilled talent and the disengagement among employees. To solve the problem, a probation periods should be taking place in an organization before turning the new employees into an official permanent staff. Probation periods serve as an evaluation period at the beginning of a new hires at their workplace. It aids in evaluate new hires based on their performance throughout the entire probationary period. This research aims to identify the problem occurs in the recruitment stage and state the purpose and benefits of probation period in terms of evaluating their role in assessing employee fit, performance, and organizational alignment. It is important to conduct an effective probation period, and the relevant ways and action had been included in the discussion part. Lastly, there is recommendation in the conclusion part and a successful recruitment process should always go through the probation period.